(untitled) (Revista de Ciências Agroveterinárias, 2017)
Milk is a food rich in its composition and widely consumed. In it, consumers seek nutrients for a healthy life, believing it to be free of contaminants and chemical residues. However, it is known that the presence of chemical waste is a common finding in milk, among them antimicrobial treatments in which the withdrawal period was not respected. Contaminated equipment, improper milking and milk adulteration and low sanitary conditions also lead to contamination with antimicrobial residue. These substances interfere in the dairy industry, generating losses and interfering with the routine laboratory tests in industries, such as phosphatase, peroxidase and reductase tests. However, the greatest risk is to human health, which can cause extensive deleterious effects such as hipersensivity processes, teratogenesis, changes in intestinal microbiota and may harm your gastromucoprotector action, as well as providing a selection of populations of highly resistant bacteria. This study aimed to raise bibliographic data about how milk contamination with antibiotics happens, their impact on society and how to control this problem.